PERAN INTERMEDIASI DAN PROFITABILITAS BANK GO PUBLIC DI BURSA EFEK INDONESIA - Nabella Permatasari, 13.05.51.0186; Nusantara, Agung (Students Journal of Economic and Management, 2017)
Economic development of a country can not be separated from the banking sector. To foster economic stability, the banking sector plays a very important. Through the banking sector, the public can trust funds to be saved and then the bank will distribute the funds in the form of loans or credits to the business sector and other parties that need. The function of banks as intermediary institutions, especially in lending has an important role for the movement of the economy as a whole and facilitate economic growth. Assessment of financial performance is one important factor for banks to determine profitability or profit earned bank. The purpose of this study was to examine the influence of Third Party Fund, Operating Expense to Operating Income, Capital Adequacy Ratio and Loan to Deposit Ratio to the profitability of banks went public listed on the Indonesia Stock Exchange during the period 2013-2015. The population of this research is the Bank Go Public in Indonesia Stock Exchange period 2013 to 2015. Data were derived from the Indonesian Stock Exchange (BEI). Samples were selected by random sampling method is 15 banking companies go public. The analysis technique used in this research is the analysis of panel data regression. The results showed that the Capital Adequacy Ratio and Loan to Deposit Ratio positive effect on return on assets, Operating Expenses to Operating Income Fund Third Party negatively affect the Return On Asset. Keyword: BOPO, CAR, DPK, LDR, ROA